Determinants Analysis of Labor Force Participation Rate in Bali Province - I Kadek Dwi Purnawan; Made Heny Urmila Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
As a developing country with one of the highest populations in the world, Indonesia possesses an abundant workforce in terms of its working-age population. Among the 38 provinces, Bali has consistently shown the highest labor force participation rate. However, a more detailed view from 2010 to 2024 reveals that the proportion of the working-age population classified as part of the labor force has experienced fluctuations. This study aims to analyze both the simultaneous and partial effects of the unemployment rate, education, and regional minimum wage on the labor force participation rate (LFPR) in Bali Province from 2010 to 2024. The study was conducted in Bali Province, using secondary data published by Statistics Indonesia (BPS). The analysis technique employed in this study is panel data regression. The results of the panel regression test indicate that the most appropriate model is the Fixed Effects Model. The findings show that the variables of unemployment rate, education, and regional minimum wage simultaneously have a significant effect on the labor force participation rate in Bali Province. Partially, the unemployment rate has a negative but insignificant effect, education has a positive and significant effect, and the regional minimum wage has a negative and significant effect on the labor force participation rate in Bali Province. It is recommended that the government and private sector collaborate in formulating appropriate policies to increase labor force participation by improving the quality of education and designing minimum wage policies that align with both labor needs and market capacity to pay wages.